Academic research for implementation of python language programs for information measurement and coding for data compression - Cesar de Souza Cavalcante, Paulo; Cavalcante de Oliveira, Williams (Seven Editora, 2023)
This article presents the expanded abstract containing information about the academic research for implementation of programs in Python language for information measures and coding for data compression. The research was conducted, at the Amazonas State University, by the student of Electronic Engineering course Williams Cavalcante Oliveira, under the guidance of Professor Paulo Cesar de Souza Cavalcante, and had its abstract presented in the 1st Amazon Stem Academy Conference 2021.  The content of the presented abstract, transcribed in this paper, exposes brief theoretical review of information measurement calculation methods and methods for statistical and dictionary-based data compression encoding. Besides other information concerning the research, it also presents, as its final product, the Python language modules developed for the execution of the algorithms of the methods studied, for performing the calculations and encodings that were the object of the research. DOI: 10.56238/pacfdnsv1-043